Late failure of posterior fixation without bone fusion for vertebral metastases - Bellato,Renato Tavares (2015)
ABSTRACTOBJECTIVE: To verify the frequency of late radiological com-plications in spinal fixation surgeries performed without fu-sion in oncological patientsMETHODS: This is a retrospective analysis analysing failure in cases of non-fused vertebral fixation in an oncology reference hospital between 2009 and 2014. Failure was defined as implant loosening or bre-akage, as well as new angular or translation deformitiesRESULTS: One hundred and five cases were analyzed. The most common site of primary tumor was the breast and the most common place of metastasis was the thoracic spine. The average follow-up was 22.7 months. Nine cases (8%) of failure were reported, with an average time until failure of 9.5 months. The most common failure was implant loosening. No case required further surgeryCONCLUSION: The occurrence of failure was not different than that reported for fused cases. The time interval until failure was higher than the median of survival of the majority (88%) of cases. Level of Evidence IV, Therapeutic Study.